A dictionary of information technology and computer science - Gunton, Tony, 1943- (Manchester, England : NCC Blakwell, 1993)
New edition of a thoughtfully prepared dictionary providing clear definitions without abandoning technical precision. Intended for both computer specialists and lay readers. Includes pronunciation only where needed. Annotation copyright Book News, Inc.
Keywords: Information technology -- Dictionaries; Computer science -- Dictionaries